Update on bovine spongiform encephalopathy - Hollis, Larry C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Bovine Spongiform Encephalopathy, commonly called “mad cow disease” by members of the media, found its way into the United States and was diagnosed in December, 2003, in a Holstein dairy cow of Canadian origin. A significant disruption to the beef cattle industry immediately followed the announcement of this finding; within a matter of weeks, however, a degree of normalcy began to return to the industry. When consumers and cattle producers alike learned of the extensive firewall system that had been put in place years earlier by the USDA and the FDA to reduce the likelihood of entry of this disease into the nation’s cow herd and into the human food supply, coupled with immediate further tightening of the control program requirements, their confidence that the threat of this disease was being handled properly was heightened.
Keywords: Beef; Bovine spongiform encephalopathy